Analisis Implementasi Teori Innovation Government dalam Mengoptimalkan Layanan Publik Partisipatif dan Kolaboratif Melalui SIPRAJA. - Pandjaitan, Petra; Huda, Nuril Qolbi; Irawan, Ninggar (LPPM STIA Lancang Kuning Dumai, 2025)
In this article, the author analyzes the implementation of the Innovation Government theory in optimizing participatory and collaborative public services through the SIPRAJA (Sidoarjo Public Service System) application. SIPRAJA is a digital innovation of the Sidoarjo Regency Government which aims to improve the efficiency, transparency, and accountability of public services in Sidoarjo. This study examines the strengths and weaknesses of the Innovation Government theory, including the encouragement of digital transformation, increasing citizen participation, and challenges such as bureaucratic resistance and the digital divide. The results of the study show that SIPRAJA has succeeded in improving the quality of public services through technology integration and multi-party collaboration, although there are still obstacles in the form of minimal digital literacy and political commitment. The recommendations proposed include strengthening socialization, increasing digital access and strengthening political will to ensure the sustainability of innovation.